DUKUNGAN KELUARGA DALAM MENINGKATKAN KUALITAS HIDUP PASIEN KANKER SERVIK (Family Support for Improving Quality Of Life in Cervical Cancer Survivor) - Susanti, Natalia Liana (JURNAL NERS LENTERA, 2017)
Introduction: Cervical cancer is a malignant disease that is caused by the Human Infection Pappiloma Virus (HPV) and holistic health problems for women around the world, including Indonesia. The family as a source of support was instrumental in providing support to improve the quality of life of cancer patients. The aim of research to determine the relationship of family support with the quality of life of patients with cervical cancer. Methods: Correlational research design with cross sectional approach. Independent variable was the support of family and dependent variable was quality of life. Population was all cervical cancer patients at the three Public Health Centre in Surabaya. Sample was cancer patients who meet the inclusion criteria of patients living with host families, the level of awareness composmentis, patients can communication fluently. Sample was chosen by purposive sampling technique. The instrument used questionnaires Likert scale that have been tested the validity and reliability. Test the hypothesis used Spearman Rank test. Result: Significant correlation between family support with the quality of life of cancer patients with cervicalcancer. A strong and direct relationship strength which means higher family support, the better quality of life for patients with cervical cancer. Discussion: Family support contribute to improved quality of life. It can be used as a reference nurses in developing palliative nursing science by involving the family as a source of social support to improve the quality of life of cancer patients